Mycobactin and clofazimine activity are negatively correlated in mycobacteria - Voskuil, Martin I.; Covey, Christopher R.; Reichlen, Matthew J.; Chatterjee, Anushila; Duerkop, Breck A.; Dawadi, Surendra; Aldrich, Courtney C.; Aaring, Alexander (Frontiers in Microbiology, 2025)
Clofazimine (CFZ) is an anti-leprosy drug shown to improve outcomes in treatment of multidrug-resistant tuberculosis (TB) and nontuberculous mycobacterial infections. Studies in Mycobacterium tuberculosis and Mycobacterium avium identified CFZ resistance mutations in the gene that encodes the MmpR5/MmpT5 regulator, which increase expression of the mycobactin (MBT) transporter, MmpS5/L5. We found exposure of M. tuberculosis to CFZ induced a pattern of gene expression that mirrored low iron conditions, including strong induction of genes that encode MBT synthesis and transport. We identified a corresponding increase in MBT levels indicating a role in iron homeostasis in CFZ activity. CFZ bactericidal activity against both Mycobacterium smegmatis and M. tuberculosis was increased in high iron conditions in which MTB synthesis and transport was limited. We show the presence of MBT correlated with decreased CFZ killing activity while inhibition of MBT synthesis increased killing. Considerable iron efflux was observed during CFZ treatment indicating iron loss may be a feature of CFZ anti-mycobacterial activity. CFZ solubility studies and CFZ-mediated reduction of free iron indicate a potential redox interaction between CFZ and iron. MBT or MBT flux across the cell envelope appears to block CFZ killing in M. smegmatis and potentially M. tuberculosis. The specific mechanism by which MBT inhibits CFZ lethality remains unclear but may involve, increased iron acquisition, the MmpS5/L5 MBT efflux pump, or the CFZ subcellular localization altered by the redox state and solubility of CFZ. CFZ has thus far been proven most effective against Mycobacterium leprae, which lacks MBT, indicating an understanding of the complex interaction of CFZ with iron acquisition systems may suggest more effective therapeutic applications.